Total antibodies and neutralizing ability of convalescent sera against three different strains of SARS-CoV-2 - Natalia V. Palyanova; Lubov S. Adamenko; Olga G. Kurskaya; Tereza A. Saroyan; Mariya V. Solomatina; Ivan A. Sobolev; Alexander M. Shestopalov (Вопросы вирусологии, 2025)
The aim of the study was to assess the level of humoral immunity to SARS-CoV-2 in COVID-19 convalescents.